Age-dependent and -independent associations between depression, anxiety, DHEAS, and cortisol: from the MIPH Industrial Cohort Studies (MICS) - Ó Hartaigh, Bríain; Loerbroks, Adrian; Thomas, G. Neil; Fischer, Joachim E.; Bosch, Jos A. (Psychoneuroendocrinology, 2012)
There is a well-established link between dysphoric mood and endocrine dysregulation, but the strength of this association may vary with age. In order to investigate this possibility we assessed anxiety and depression with overnight urinary cortisol and plasma dehydroepiandrosterone-sulphate (DHEAS) in 608 factory employees ranging between 21 and 62 years. As expected, DHEAS declined with age (r = À0.54, P < 0.001) while there was a modest age-related increase in nocturnal cortisol (r = 0.17, P < 0.001). Depressive symptoms were associated with higher nocturnal cortisol (b = 0.19, P < 0.001), independent of age. While the association between anxiety and cortisol (age by anxiety interaction: b = 0.11, P < 0.05) became stronger with age, there was a similar decline in the DHEAS/cortisol ratio in high-anxious middle-aged adults (b = À0.10, P = 0.018). The current ﬁndings suggest that dysphoric mood, and in particular anxiety, may exacerbate the effects of aging on cortisol release. Prospective studies are needed to determine the causal relations between dysphoric mood, cortisol and DHEAS across the lifespan.